1974
DOI: 10.1038/bjc.1974.98
|View full text |Cite
|
Sign up to set email alerts
|

Serum Oestradiol-17β in Normal Women

Abstract: Summary.-Serum concentrations of oestradiol-17/ were measured by radioimmunoassay during 40 menstrual cycles from 38 normal premenopausal women. Repeated samples were studied from 25 normal postmenopausal women. The method was highly specific and extremely sensitive. In premenopausal women the pattern of serum oestradiol-17/ was remarkably constant but the concentrations varied with age. Women in the fourth decade of life had significantly higher concentrations of oestradiol-17/ than either younger or older wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1974
1974
1990
1990

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…England et al (1974) also found an increase in plasma oestradiol levels with increasing age in normal premenopausal women, but the increase was restricted to the luteal phase. Further data are clearly required.…”
Section: Resultsmentioning
confidence: 78%
“…England et al (1974) also found an increase in plasma oestradiol levels with increasing age in normal premenopausal women, but the increase was restricted to the luteal phase. Further data are clearly required.…”
Section: Resultsmentioning
confidence: 78%
“…In a previous study (England et al, 1974) (England et al, 1974). The addition of two more since this publication has not None of the subjects studied had a history of gynaecological disease or was taking any hormonal preparation.…”
mentioning
confidence: 93%
“…Measurement of serum oestradiol-173.-Radioimmunoassay of oestradiol-17/3 was carried out by the method described previously (Cameron and Jones, 1972;England et al, 1974). By counting the radioactive supernatant sample (0.5 ml) in 10 ml of a 1 : 1 dilution with Scintillator Grade Xylene of PCS-Liquid scintillation cocktail (Hopkins and Williams, Chadw%Aell Heath, Essex) counting efficiency was rasied to approximately 38%o.…”
mentioning
confidence: 99%
“…Serum oestradiol was measured by radioimmunoassay as published elsewhere (England et al, 1974 (Siegel, 1956 Mean concentration for serum oestradiol in adult women (luteal phase): 67-3 ± 1-47 (se mean) pg/ml.…”
Section: Methodsmentioning
confidence: 99%